Sifat Fisika Dan Mekanika Papan Partikel Dari Kayu Durian (Durio zibethinus Murr): The Physical and Mechanical Properties of Particle Board from Durian Wood (Durio zibethinus Murr) - Indrayanti, Lies; Siska, Grace; Wahyudi, Wahyudi; Setiarno, Setiarno; Sianipar, L. (HUTAN TROPIKA, 2024)
The studi aimed to determine the characteristics particle board of Durian Wood. The material used durian wood which is no longer productive. The adhesive used is PVAc adhesive. The research method used a Completely Randomized Design with a single factor, namely particle size with 3 levels, namely 4.5 and 6 mesh. The parameters tested, namely the physical and mechanical properties of the board, refer to the SNI 03-2105-2006 standard. The results showed that the average water content ranged from 16.94–17.25%, density 0.134–0.145 g.cm-3, water absorption capacity 2.09– 2.50%, thickness expansion 10.93–15.25% , while MoE 65629.90-79209.38 kgf.cm-2, MoR 267.86 – 431.33 kgf.cm-2, internal bond strength 0.08–0.15 kgf.cm-2, Screw holding strength 0.021 –0.035 kgf. Thickness development at the 5 mesh level, Modulus of Elasticity (MoE), and Modulus of Ropture (MoR) have met the SNI 04-2105-2006 standards, while the water content, density, water absorption capacity, internal adhesive strength and Screw holding strength still do not meet the standards set. The highest MoE reached 125,000 kgf.cm-2 and MoR reached 643 kgf.cm-2. The results of mechanical tests show that particle board of durian wood has the potential to be used as interiors construction.